Meningkatkan Pemasaran Dodol Bali di Desa Kesiut Kecamatan Kerambitan Kabupaten Tabanan - Ni Putu Sukanteri; Putu Fajar Kartika Lestari; Ida Ayu Dwi Susanti; Luh Putu Kirana Pratiwi (Konsienti : Community Services Journal, 2023)
Kesiut Village, Kerambitan District, Tabanan Regency is one of the villages where there is a Women's Group producing Balinese dodol. The aims of the service are: to increase group administrative knowledge, to increase members' knowledge of consumer wants and needs, to improve the skills of group members in marketing Balinese dodol. Increase member income in the future through product marketing analysis. Community service is carried out in Kesiut Village, Kerambitan District, Tabanan Regency. The implementation of this service is carried out in an effort to increase the knowledge and skills of group members in managing processed products and preparing products ready for market. Based on the results of implementing community activities in the Merta Sari Werdhi Group in Kesiut Village, it shows that: There was an increase in the knowledge of group members before and after the socialization was carried out by 90% in product labeling and product packaging. The skills of group members increased by 90%. This shows that the existence of socialization and training provides increased knowledge and skills of group members. Processed Balinese dodol products made by group members before and after mentoring show a clear change in identity.